2009
DOI: 10.1037/a0013484
|View full text |Cite
|
Sign up to set email alerts
|

Reading polymorphemic Dutch compounds: Toward a multiple route model of lexical processing.

Abstract: This paper reports an eye-tracking experiment with 2500 polymorpemic Dutch compounds presented in isolation for visual lexical decision, while readers' eye-movements were registered. We found evidence that both full-forms of compounds (dishwasher) and their constituent morphemes (e.g., dish, washer, er) and morphological families of constituents (sets of compounds with a shared constituent) played a role in compound processing. We observed simultaneous effects of compound frequency, left constituent frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

44
218
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(265 citation statements)
references
References 84 publications
(163 reference statements)
44
218
0
3
Order By: Relevance
“…This means that the present experiment and the auditory lexical decision experiment of Balling and Baayen (2008) are consistent in showing an interaction between whole-word and second constituent frequency. Similar interactions between whole-word and constituent frequencies are reported by Kuperman et al (2009) and Kuperman, Bertram, and Baayen (2010).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This means that the present experiment and the auditory lexical decision experiment of Balling and Baayen (2008) are consistent in showing an interaction between whole-word and second constituent frequency. Similar interactions between whole-word and constituent frequencies are reported by Kuperman et al (2009) and Kuperman, Bertram, and Baayen (2010).…”
Section: Resultssupporting
confidence: 78%
“…While in visual lexical decision and reading, a greater family size leads to shorter response latencies and shorter fixation durations (De Jong, Schreuder, & Baayen, 2000;Kuperman, Schreuder, Bertram, & Baayen, 2009), in auditory lexical decision onset-aligned family members sharing the first (but not the second) morpheme have an inhibitory effect. It is only those family members that are fully consistent with all bottom-up information at word offset, the continuation forms, that show the facilitation familiar from the reading literature.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have looked at the processing of compounds and their constituents using an eye-tracking paradigm (Kuperman, Bertram, & Baayen, 2008;Kuperman, Schreuder, Bertram, & Baayen, 2009). Such research has found evidence for parallel access to full forms (blackboard) and their constituents (black and board).…”
mentioning
confidence: 99%
“…Recent proposals based on experiments provide evidence of the inadequacy of sublexical and supralexical models, as well as dual-route models designed as a 'horse race', as demonstrated by Pollatsek et al (2008). Kuperman et al (2008Kuperman et al ( , 2009Kuperman et al ( , 2010 proposed a multiple-route model as an alternative. According to these authors (2010: 94), the model considers the mental lexicon as a "long-term memory storage for lexical information".…”
Section: Processing Of Morphological Complex Wordsmentioning
confidence: 99%
“…Baayen (2007); Kuperman et al (2009) ;Kuperman, et al (2010)). Although a direct route is most efficient for the processing of high-frequency complex words (e.g.…”
Section: Processing Of Morphological Complex Wordsmentioning
confidence: 99%